Choosing how to boost waxy crude line flow depends on oil's qualities - El-Emam, Nour A; Bayoumi, Abdel Wahab A; El-Gamal, Ismail M; Abu-Zied, A (The Oil & gas journal, 1993)
Dilution by either gasoline or kerosine proved more effective than heating or the addition of flow improving chemicals in studies of methods for improving pipeline flow of waxy crudes. Additionally, a computer program was developed that calculates the pressure-loss reduction resulting from the improved flow properties of the tested crudes regardless of the method used. This program led to the conclusion that dilution by gasoline is the best technique for one type of waxy crude represented by GPY-3, while heating is the best method for the other 2 crude types represented by M-96 and Khalda. Experiments testing the different dilution techniques are detailed.